Global fairness beliefs: Steps beyond the disability - Perrino, Andrea L (University of Ottawa (Canada), 2004)
In the past, people with disabilities were not encouraged to participate in physical activity beyond that of rehabilitation. As such, this group has been covertly and overtly excluded from participating in the development of a healthy lifestyle. This paper explored the factors leading to the exclusion of people with disabilities from the physically active community. The scope of justice literature was reviewed, and this area of research was taken further with the exploration of global fairness beliefs. This orientation toward others launches from previous research (e.g., Deutsch,1985; Opotow, 2000) and involves a set of beliefs (the belief that considerations of fairness apply to others, the belief in the allocation of a share of community resources to others, and belief in sacrificing to foster others well-being), which are argued to be relatively stable and fundamental to our behaviours. The first study tested a measure of global fairness beliefs (N = 206). The measure appeared to be sound with a strong one-factor model produced. The first study also showed that the measure had relatively good test-retest reliability as well as external and discriminant validity. Considering previous research (e.g., Opotow, 1994), the goal of the second study was to evaluate the moderating role of situations of conflict, dissimilarity and lack of utility in the relationship between global fairness beliefs and exclusionary attitudes and behavioural intentions toward people with disabilities within the fitness and physical activity community. A total of 282 participants were presented with scenarios depicting situations of high or low conflict, similarity and utility. Results showed little support for the hypotheses and some unexpected outcomes. Limitations of the current study, and future studies are proposed. Applications to the acceptance of people with disabilities both within the active community and beyond are discussed. Finally, the important influence that global fairness beliefs exert in the trends of the social world is discussed.
Keywords: Psychology, Social.